Icebreakers in Anglo-Russian Relations (1914-21) - Saunders, David (International history review, 2016)
Foreign supply to Russia in the First World War is familiar terrain, but although the present paper engages to some degree with the military, diplomatic, and especially economic aspects of the subject, its primary affiliations lie elsewhere. Its principal purpose is to discuss the icebreakers on which it concentrates not only just before but also just after Russia's withdrawal from the First World War, with a view to contrasting the first phase of the ships' history with the second and so highlighting the perennially ambivalent character of the Anglo-Russian relationship. On the way, it touches on questions of geography, English local history, environmental history, the history of technology, and, even, towards the end, Russian literary history.